Comparative evaluation of SRF and RDF co-combustion with coal in a fluidised bed combustor - Garg, A.; Smith, Richard; Longhurst, Philip J.; Pollard, Simon J. T.; Simms, Nigel J.; Hill, D. (Cranfield University, 2007)
The experimental study reported here was carried out to assess the feasibility of municipal solid waste (MSW) derived solid recovered fuel (SRF) in energy recovery applications. SRF was prepared by grinding and blending the major MSW constituents such as paper, plastics, wood and textile. The percentage of various constituents was the same as from the Ecodeco process employing bio- drying followed by mechanical treatment. The heating value of synthetic SRF was ca. 21 MJ/kg (as received basis). The metal emission results from the SRF co- combustion with coal were compared with that obtained from coal mono-combustion and refuse derived fuel (RDF) co-combustion with coal. RDF was also derived from MSW and was obtained from a local mechanical treatment waste facility. Use of SRF as co-fuel does not increase the emissions of metals to the environment in the flue gas stream when compared to coal mono-combustion. In addition, use of MSW derived fuel reduces the arsenic release to the atmosphere. The results showed that most of the metals are retained in the ash components (except mercury). The mobility of metals depends on the volatility and type of feedstock.